Comparison of induction strategies and responses for acute myeloid leukemia patients after resistance to hypomethylating agents for antecedent myeloid malignancy. (June 2020) - Talati, Chetasi; Goldberg, Aaron D.; Przespolewski, Amanda; Chan, Onyee; Ali, Najla Al; Kim, Jongphil; Famulare, Chris; Sallman, David; Padron, Eric; Kuykendall, Andrew; Lancet, Jeffrey E.; Wang, Eunice; et al.
Highlights: Poor outcomes to induction chemotherapy in sAML are common after HMA treatment. We investigated outcomes of induction regimens (CLAG/M, 7 + 3, CPX-351) in sAML after HMA exposure. ORR was higher with CLAG/M (53%) compared to 7 + 3 (32%, p 0.01) and similar to CPX-351 (41%, p 0.04). Despite higher response rates with CLAG/M, no significant difference in the mOS was noted. Our study illustrates the unmet need for more efficacious therapy for sAML after HMA failure. Abstract: Outcomes in patients with secondary acute myeloid leukemia (sAML) (including therapy related myeloid neoplasms and AML with myelodysplasia related changes (MRC)) are poor. Patients treated with hypomethylating agents (HMAs) for antecedent hematological malignancy (AHM) have suboptimal responses to induction chemotherapy upon transformation to AML. We investigated outcomes after various induction strategies in patients with sAML who had prior HMA exposure. We identified 242 patients with sAML who had prior HMA treatment for AHM and later received induction chemotherapy upon AML transformation and divided into 3 cohorts based on induction regimen: (A) CLAG/M (B) 7 + 3 and (C) CPX-351. The CR/CRi rate was 53% in cohort A, 32% in cohort B and 41.2% in cohort C (p = 0.005 between cohort A and B) (p = 0.329 between cohorts A and C) (p = 0.402 between cohorts B and C). The early death rates were not significantly different among the three cohorts (p = 0.200). In patients who received ≤4 cycles of HMAs prior to AML transformation, response rates to CPX-351 were higher (64.3%) with a trend toward better overall survival (OS) (19.9 vs. 5.5 months) compared to >4 cycles (p = 0.092). There was no significant difference in median OS among the 3 groups: cohort A (7.27 months), cohort B (7.63 months) and cohort C (7.07 months) (p = 0.887). We demonstrate that CLAG/M and CPX-351 yield higher CR/CRi rates compared to 7 + 3 in patients with sAML after HMA failure. Median OS remains poor and did not differ among the 3 groups, illustrating the unmet need for more efficacious therapy for sAML patients following HMA failure.